Penerapan Pendekatan Culturally Responsive Teaching (CRT) dengan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar IPAS Kelas IV SD N. 060931 Medan - Purba, Saida; Sari, Dwi Novita; Juwita, Putri; Siregar, Sakinah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to improve student learning outcomes by applying the Culturally Responsive Teaching (CRT) approach in Science and Social Studies, focusing on biodiversity and culture in the surrounding environment for fourth-grade students at SD Negeri 060931 Medan. This research is a classroom action study involving 16 students. Data collection techniques include pre-tests and post-tests, with a test instrument designed to measure students' knowledge. Data analysis is conducted both quantitatively and qualitatively. In Cycle 1, the results showed that none of the students met the Minimum Completeness Criteria of 75, with an average score of 49.1. In Cycle 2, there was a significant improvement, with 14 out of 16 students achieving completeness and an overall average score of 83.43. This research concludes that using the Culturally Responsive Teaching (CRT) approach can effectively enhance the learning outcomes of fourth-grade students at SD Negeri 060931 Medan in the Natural and Social Sciences subject